Analisis Pelaksanaan Kebijakan Bantuan Program Keluarga Harapan - Faizal Anwar; Nanik Untari (JOPPAS: Journal of Public Policy and Administration Silampari, 2020)
ABSTRACT The purpose of this study was to determine the implementation of the Family Hope Program Assistance Policy and to want to know what factors hindered the implementation of the Family Hope Program (PKH) in Mesigit Village. The method in this research uses qualitative research. The results showed that the implementation of the Family Hope Program policy has gone well, but that has become an obstacle in the implementation of the Hope Family Program coordinating PKH facilitators to the village government. The conclusion of this research is that the implementation of the Family Hope Program (PKH) has been going well because it has four indicators of policy implementation such as: communication, resources, disposition and bureaucratic structure. While the inhibiting factors are the awareness and interest of the community about PKH, telecommunications network facilities and the absence of meeting activities, there is no coordination from PKH facilitators. Keywords: Policy, Poverty, Program.